Pengaruh Penerapan Metode Game Based Learning Berbasis Ice Breaking Terhadap Suasana Belajar Peserta Didik Pada Mata Pelajaran PPKn - Widyana, Widyana (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
This research is motivated by several problem factors that occur during the learning process, namely: 1) lack of teacher variation in classroom learning activities 2) use of makeshift media by teachers in the teaching and learning process 3) the learning atmosphere in the classroom is easily boring 4) teachers are less proficient in creating or making learning media that attract students' attention 5) the availability of school facilities is inadequate. The purpose of this study was to determine the effect of the application and student responses to the treatment of the game based learning method based on ice breaking to build a more enjoyable learning atmosphere in the PPKn subject for class VII students at SMP Negeri 1 Padarincang. The research method used by the researcher is the quantitative experimental method. From the results of the hypothesis test, namely with the t-test, a significance value of 0.000 was obtained, where 0.000 is smaller than 0.05 or can be written as a sig value of 0.000 <0.05. Thus, it can be concluded that there is an effect of the application of ice breaking to build a learning atmosphere in the PPKn subject, the results of the research that the author studied at SMP Negeri 1 Padarincang using the Ice breaking learning method made students more enthusiastic, active and not easily sleepy during learning.